2010
DOI: 10.4155/bio.10.70
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Quantification of a Therapeutic Domain Antibody Using Ultra-Performance Liquid Chromatography–Mass Spectrometry and Immunoassay

Abstract: The two assays show good correlation (r(2) = 0.92), giving confidence in using either method for quantification of the dAb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…There is no need to always have both LBA and LC-MS assays developed in parallel even though bioanalysts tend to do that during the initial stages of method development. It has been reported that the results generated by both types of assays have good agreement with each other in most cases from a statistical point of view [39,50,52]. In some cases, however, due to the complexity and diversity of emerging biologics drug portfolios, as discussed before, it is becoming a necessity to have both sets of data from LBA and LC-MS assays to provide complementary information to aid better decision making.…”
Section: Cases When Both Lba and Lc-ms Assay Are Recommendedmentioning
confidence: 88%
“…There is no need to always have both LBA and LC-MS assays developed in parallel even though bioanalysts tend to do that during the initial stages of method development. It has been reported that the results generated by both types of assays have good agreement with each other in most cases from a statistical point of view [39,50,52]. In some cases, however, due to the complexity and diversity of emerging biologics drug portfolios, as discussed before, it is becoming a necessity to have both sets of data from LBA and LC-MS assays to provide complementary information to aid better decision making.…”
Section: Cases When Both Lba and Lc-ms Assay Are Recommendedmentioning
confidence: 88%
“…Historically, this technique has proven to be robust for use during the quantitation of drugs and can be automated for sample preparation in various formats (e.g., 96well plate or online). In a recent example, SPE was successfully used as a sample prepara tion approach for the quantitation of a 13 kDa domain antibody, providing a detection limit in the low ng/ml when combined with short LC-MS/MS ana lysis [18]. In this particular example, SPE was successfully employed in a whole protein LC-MS/MS workflow, as well as an alternative approach involving the SPEbased cleanup of a tryptic digest of the same domain antibody.…”
Section: Sample Preparation and Analyte Purificationmentioning
confidence: 95%
“…For instance, Neubert et al () developed a magnetic bead‐based immunoprecipitation method to quantify an anti‐drug antibody (ADA) with the existence of therapeutic proteins in monkey and human plasma, and considerably facilitated the immunogenicity investigation of an mAb. The parallel use of LBA and LC‐MS can also reveal specific pharmaceutical information such as biological activity and molecular integrity of biotherapeutics (Szapacs, Urbanski, & Kehler, ). For example, LBA and LC/MS have been applied to determine separately the concentrations of mAbs and unconjugated drugs in ADC bioanalysis (Kaur, ).…”
Section: Quantification Of Biotherapeutics In Biomatricesmentioning
confidence: 99%